GAMBARAN PENGGUNAAN KATA AING OLEH NON-NATIVE SUNDA DALAM KONTEKS RELASI PERTEMANAN - Resti Arsanti; Nabilah Hasna; Putri Astuti; Yuliana Hanami (Jurnal Sosial Humaniora, 2023)
Sojourn students will be faced with a new environment and culture. Interaction with native speakers of the regional language can be a factor that supports the form of adjustment in a new environment. The word “aing” as a first-person pronoun is part of the very rough level of Sundanese that should not be used carelessly. Apart from this meaning, it turns out that the use of the word foreign is often found among students in the Sundanese area. This study aims to determine how the description of the use of the word foreign by non-native Sundanese in the context of friendship relations. Through a qualitative approach, this research involved 36 non-native Sundanese students. Data collection was carried out by distributing a self-report questionnaire in the form of a Google Form consisting of 14 questions in the form of an open-ended question. The data obtained are interpreted into four discussion categories, namely "Understanding and Practice of Using Foreign Words", "Background for Using Foreign Words", "Offline & Online Interaction", and "Impact of Using Foreign Words". The results show that sojourn students understand when and how aing was used in friendly relations. This makes them more able to feel the positive impact on the friendships that are built when using aing in communication.